Pengaruh Digital Leadership Terhadap Efisiensi Kinerja Dimediasi Oleh Digitalisasi Layanan Di Bea Dan Cukai Tmp B Palembang - Sinta Wulandari; Sulaiman Helmi (CV. ITTC INDONESIA, 2026)
This study aims to analyze the effect of digital leadership on performance efficiency mediated by service digitalization at Bea dan Cukai TMP B Palembang. Digital transformation in public organizations requires leadership capable of directing the effective use of technology to enhance organizational performance. This research employs a quantitative approach using a survey method by distributing questionnaires to 47 employees of Bea dan Cukai TMP B Palembang. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that digital leadership has a positive and significant effect on service digitalization and performance efficiency. Furthermore, service digitalization is proven to act as a mediating variable that strengthens the influence of digital leadership on performance efficiency. These findings emphasize that the success of improving performance efficiency in public institutions largely depends on digital leadership supported by the optimal implementation of technology-based services.